2021
DOI: 10.3390/nano11081963
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Internalization Efficiency of Macrophages from Adsorbed Nanoparticle-Based Monolayers

Abstract: Functional coatings based on the assembly of submicrometric or nanoparticles are found in many applications in the biomedical field. However, these nanoparticle-based coatings are particularly fragile since they could be exposed to cells that are able to internalize nanoparticles. Here, we studied the efficiency of RAW 264.7 murine macrophages to internalize physisorbed silica nanoparticles as a function of time and particle size. This cell internalization efficiency was evaluated from the damages induced by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Studies have suggested that particle sizes less than <20 nm have high mobilities that influence particle surface charge. In this study, the particle sizes ranged from 300 to 400 nm, which showed less mobility, thereby indicating more sustainability [23,24]. Based on cumulative and distribution fit analyses of particles, the LRPDNV formulation was of high quality in a colloidal injectable formulation, with 100% linearity (Figure 1E,F).…”
Section: Dynamic Light Scattering (Dls) Analysismentioning
confidence: 70%
“…Studies have suggested that particle sizes less than <20 nm have high mobilities that influence particle surface charge. In this study, the particle sizes ranged from 300 to 400 nm, which showed less mobility, thereby indicating more sustainability [23,24]. Based on cumulative and distribution fit analyses of particles, the LRPDNV formulation was of high quality in a colloidal injectable formulation, with 100% linearity (Figure 1E,F).…”
Section: Dynamic Light Scattering (Dls) Analysismentioning
confidence: 70%
“…Compared to MPs and macroplastics (MAPs), NPs present different physicochemical and biological properties; however, their environmental measurements are hardly available [ 53 ]. It is known that the size of the particle strongly influences cell–particle interaction [ 54 ]; however, there is a lack of information regarding the individual role of their size, surface chemistry, and shape in the cellular internalization.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to circumvent total macrophage clearance could be explained by the physicochemical characteristics of the formulation. Both PEI and VIPER polyplexes show sizes below 100 nm, while macrophages are known to most efficiently take up particles with sizes above 200 nm [ 54 ]. Additionally, the large surface area covered by type II pneumocytes as well as the corona of adsorbed biomolecules [ 55 ] could favor the contact with the aerosolized polyplexes.…”
Section: Sirna/viper Polyplexes Activity Against Wild-type Sars-cov-2...mentioning
confidence: 99%